Pengaruh Kompensasi dan Budaya Kerja Terhadap Produktivitas Kerja Karyawan Pada Perusahaan Kecap Segi Tiga Majalengka (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2020)
The purpose of this study was to determine compensation, work culture, work productivity of employees at Segi Tiga Majalengka Company. The large influence of compensation influenceon employee work productivity at Segi Tiga Segi Tiga Majalengka Company, has a biginfluence on the influence of work culture on employee work productivity at Segi Tiga SegiTiga Majalengka Company, and to know the big influence of influence and culture onemployee work productivity at Segi Tiga Majalengka Company.The method used is a survey method with descriptive analysis techniques and verification. Thedata technique was carried out by interviewing, presenting a questionnaire, and studyingliterature. The validity test is done by comparing the Corrected Item - Total Correlation valuewith the r table value and reliability testing using the Croncbach Alpha formula. The dataanalysis design used Data Normality Test Analysis, Determination Coefficient Analysis, t testand f test.The results of this study indicate that compensation has a significant effect on employeeproductivity. Work culture has an effect but not significantly on employee work productivity.Compensation and work culture together have a significant effect on employee workproductivity.